Cut off from River, but rich in biodiversity: fish biodiversity and livelihood of fishermen in Jhapa baor, Jashore, Bangladesh (Asian Journal of Medical and Biological Research, 2022)
Oxbow lake is one of the significant freshwater fisheries assets in Bangladesh, which supports livelihood of fishermen community. This study was conducted to assess the fish biodiversity and socio-economic conditions of fishermen in Jhapa baor (oxbow lake) at Manirampur upazilla in Jashore district from July to September 2019. This investigation used primary data, collected through household interviews, key informant or cross-checked interviews, Focus Group Discussion (FGDs) as well as secondary data. Fish fauna were identified based on their morphometric and meristic characters. After identification, fish species were systematically classified. A total of 43 species belonged to 11 orders and 17 families were identified from the baor. A total of five types of nets, three types of fish traps and four types of wounding gears were found during the survey. Furthermore, results of this study didn't show improved socio-economic conditions of the baor fisheries dependent families. Their income was less than the national average. Almost 50% of the households had up to 4 family members. Most family had single earning member. Most didn't have land aside from residence and their houses were earthen made. Although most of them had access to safe drinking water, few had access to quality health services and sanitary latrine. Their education levels were low about 70% fishers had no or beneath primary level education. Although currently the majority of their children were school going (72%) and the percentage is increasing gradually. Almost 65% of fishing community was involved with credit organization. This study will provide the baseline information about biodiversity and livelihood status of fishermen in Jhapa baor.Asian J. Med. Biol. Res. 2022, 8 (4), 194-215